Towards Sustainable Wastewater Reuse in the Middle East and North Africa - Abu-Madi, Maher; Al-Sa'ed, Rashed (Consilience, 2009)
Water has a precious value, and each drop must be accounted for in water scarce regions such as the Middle East and North Africa. Therefore, wastewater has to be reclassified as a renewable water resource rather than as waste. This helps in augmenting water availability, and at the same time in preventing environmental pollution. Utilization of this resource requires collection, treatment, and use of all generated wastewater. Although reuse of wastewater is recognized in most water-scarce countries, the reuse of wastewater is still very low. This paper analyzes the major components of a sustainable wastewater reuse scheme. It also reviews the different methods that are frequently used to quantify and report progress and achievements in wastewater reuse. The paper also introduces an alternative yardstick named by the author as the Wastewater Reuse Index (WRI) that has a value between 0-100; WRI is calculated by dividing the amounts of wastewater being actually reused by the total amounts of wastewater generated at country level. WRI enables water resource managers and policymakers to put a figure on the gap between achievements at different junctures. Moreover, WRI recognizes water saving efforts such as low water consumption and reducing losses; thus, WRI highlights the way forward for improving the reuse efficiency as an integral part of water resources management. The paper highlights the major barriers to extensive reuse of the reclaimed wastewater in the MNEA countries.